Comparative Analysis of Hepatitis C Virus Pathogenicity in Different Genotypes: Implications for Disease Progression and Treatment Outcomes - Alanazi, Abdullah; Abdullah, Erlina (Journal of Cultural Analysis and Social Change, 2025)
Hepatitis C virus (HCV) remains a significant global health challenge due to its remarkable genetic diversity, with seven genotypes and numerous subtypes that influence disease progression and treatment outcomes. This systematic review synthesizes evidence on the pathogenicity, clinical implications, and therapeutic responses associated with different HCV genotypes. The high mutation rate and quasispecies dynamics of HCV enable immune evasion and resistance development, complicating efforts to create a universal vaccine. Genotype-specific differences were observed in disease progression, with genotype 3 linked to hepatic steatosis and accelerated fibrosis, while genotype 1 exhibited greater resistance to interferon-based therapies but improved outcomes with direct-acting antivirals (DAAs). Despite DAAs achieving cure rates exceeding 90% for most genotypes, challenges persist for genotypes like 3, 4, and 5, which require further research to optimize therapeutic strategies. Host factors, including IL28B and IFNL4 polymorphisms, were identified as significant predictors of treatment success, influencing sustained virologic response (SVR) rates and disease outcomes. Technological advancements such as next-generation sequencing (NGS) have enhanced genotype identification and resistance monitoring, facilitating personalized treatment approaches. However, the high cost of DAAs limits accessibility in resource-limited regions, exacerbating global health disparities. The review underscores the need for expanded research into underrepresented genotypes, innovative vaccine strategies, and equitable access to therapies. Integrating viral, host, and technological insights will be crucial for advancing personalized medicine and achieving global HCV elimination.